The time course of the transcriptomic response of Sinorhizobium meliloti 1021 following a shift to acidic pH - Hellweg, Christoph (BioMed Central, 2009)
BACKGROUND: The symbiotic soil bacterium Sinorhizobium meliloti often has to face low pH in its natural habitats. To identify genes responding to pH stress a global transcriptional analysis of S. meliloti strain 1021 following a pH shift from pH 7.0 to pH 5.75 was carried out. In detail, oligo-based whole genome microarrays were used in a time course experiment. The monitoring period covered a time span of about one hour after the pH shift. The obtained microarray data was filtered and grouped by K-means clustering in order to obtain groups of genes behaving similarly concerning their expression levels throughout the time course. RESULTS: The results display a versatile response of S. meliloti 1021 represented by distinct expression profiles of subsets of genes with functional relation. The eight generated clusters could be subdivided into a group of four clusters containing genes that were up-regulated and another group of four clusters containing genes that were down-regulated in response to the acidic pH shift. The respective mean expression progression of the four up-regulated clusters could be described as (i) permanently and strong, (ii) permanently and intermediate, (iii) permanently and progressive, and (iv) transiently up-regulated. The expression profile of the four down-regulated clusters could be characterized as (i) permanently, (ii) permanently and progressive, (iii) transiently, and (iv) ultra short down-regulated. Genes coding for proteins with functional relation were mostly cumulated in the same cluster, pointing to a characteristic expression profile for distinct cellular functions. Among the strongest up-regulated genes lpiA, degP1, cah, exoV and exoH were found. The most striking functional groups responding to the shift to acidic pH were genes of the exopolysaccharide I biosynthesis as well as flagellar and chemotaxis genes. While the genes of the exopolysaccharide I biosynthesis (exoY, exoQ, exoW, exoV, exoT, exoH, exoK exoL, exoO, exoN, exoP) were up-regulated, the expression level of the flagellar and chemotaxis genes (visR, motA, flgF, flgB, flgC, fliE, flgG, flgE, flgL, flbT, mcpU) simultaneously decreased in response to acidic pH. Other responding functional groups of genes mainly belonged to nitrogen uptake and metabolism (amtB, nrtB, nirB, nirD), methionine metabolism (metA, metF, metH, metK, bmt and ahcY) as well as ion transport systems (sitABCD, phoCD). It is noteworthy, that several genes coding for hypothetical proteins of unknown function could be identified as up-regulated in response to the pH shift. CONCLUSION: It was shown that the short term response to acidic pH stress does not result in a simple induction or repression of genes, but in a sequence of responses varying in their intensity over time. Obviously, the response to acidic pH is not based on a few specific genes, but involves whole sets of genes associated with various cellular functions.